Clinical Efficacy and Safety Profile of Micropulse Transscleral Cyclophotocoagulation in Refractory Glaucoma. Issue 5 (May 2018) - Williams, Alice L.; Moster, Marlene R.; Rahmatnejad, Kamran; Resende, Arthur F.; Horan, Teresa; Reynolds, Michael; Yung, Edward; Abramowitz, Benjamin; Kuchar, Sarah; Waisbourd, Michael
Abstract : Purpose: To investigate the clinical efficacy and safety profile of micropulse transscleral cyclophotocoagulation (MP-CPC) in patients with refractory glaucoma. Materials and Methods: Retrospective case series of 79 consecutive patients who underwent MP-CPC at the Wills Eye Hospital from March 23, 2014 to June 23, 2016 and who had at least 3 months of follow-up. Treatment success was defined as an intraocular pressure (IOP) of 6 to 21 mm Hg or a reduction of IOP by 20%. Failure was defined as an inability to meet the criteria for success, need for retreatment >3 times, or need for incisional glaucoma surgery. Results: Patients had a mean follow-up time of 7.8±4.5 months. The mean IOP before MP-CPC was 31.9±10.2 mm Hg. The IOP was reduced by an average of 51% at the last follow-up and the mean number of IOP lowering medications was reduced from 2.3 at baseline to 1.5 at last follow-up. Treatment success rates were 75% at 3 months, 66% at 6 months, and 67% at last follow-up. Complications of MP-CPC included 7 patients with hypotony (8.8%), 21 patients with prolonged anterior chamber inflammation (1+ cell or flare for >3 mo, 26%), 13 patients with loss of ≥2 lines of best-corrected visual acuity at 3 months (17%), 4 patients with macular edema (5%), 2 patients with corneal edema and 2 patients with phthisis. Conclusions: MP-CPC is an effective treatment for patients with refractory glaucoma. Shorter treatment times with more frequent repeat treatments, if necessary, should be considered given the incidence of significant vision loss in this study.